2006
DOI: 10.2298/vsp0604349k
|View full text |Cite
|
Sign up to set email alerts
|

Detection of free cancer cells in peritoneal cavity in patients surgically treated for gastric adenocarcinoma

Abstract: Peritoneal lavage cytology was shown to be a useful tool for the detection of the group of patients with greatest risk of peritoneal dissemination. The frequency of positive cytological findings was highly associated with the diameter of the tumor and the cancer invasion of serosa. Cytological examination of peritoneal lavage fluid improved the accuracy of staging and selection of patients who might have benefit from neoadjuvant chemotherapy.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

1
8
0

Year Published

2011
2011
2020
2020

Publication Types

Select...
4
4

Relationship

0
8

Authors

Journals

citations
Cited by 16 publications
(9 citation statements)
references
References 34 publications
1
8
0
Order By: Relevance
“…In one of the earlier study, Kostić et al [8] showed that a tumor diameter >5 cm, tumor invasion of serosa, histopathological stage of the disease III and IV, and macroscopically visible metastases were the most important risk factors for detection of free cancer cells in patients surgically treated for gastric adenocarcinoma. The exact mechanism that was contributing to microscopic peritoneal carcinomatosis was still not clear.…”
Section: Discussionmentioning
confidence: 98%
“…In one of the earlier study, Kostić et al [8] showed that a tumor diameter >5 cm, tumor invasion of serosa, histopathological stage of the disease III and IV, and macroscopically visible metastases were the most important risk factors for detection of free cancer cells in patients surgically treated for gastric adenocarcinoma. The exact mechanism that was contributing to microscopic peritoneal carcinomatosis was still not clear.…”
Section: Discussionmentioning
confidence: 98%
“…For the subgroup analysis, conventional cytology studies 1-3,12,16-19,24,49,54,79,94,96 (risk difference: 0.34; 95% CI: 0.2–0.48; n=2,373 patients; I 2 =93%; p <0.00001) and PCR-CEA 31,36,38,49,77,93,94,97,104 (risk difference: 0.5; 95% CI: 0.36–0.63; n=1,073 patients; I 2 =83%; p <0.00001) were reviewed by comparing stage III or IV patients with stage I or II patients.…”
Section: Resultsmentioning
confidence: 99%
“…For the subgroup analysis, conventional cytology studies 1-3,12,14,16,18,19,25,29,41,43,46,51,52,54-57,61,63,78,81,92,94,96, (risk difference: 0.25; 95% CI: 0.18–0.31; n=5,008 patients; I 2 =87%; p <0.00001) and PCR-CEA 31,36,38,48,57,58,64,76,77,93,94,97,101,104 (risk difference: 0.3; 95% CI: 0.15–0.45; n=1,464 patients; I 2 =93%; p <0.00001) were reviewed.…”
Section: Resultsmentioning
confidence: 99%
See 1 more Smart Citation
“…Other means of peritoneal dissemination include iatrogenic or spontaneous perforation of the primary cancer 10 or embolism from transected lymphatics and blood vessels during the course of surgical resection 11 . Spread of the cancer cells in the peritoneal cavity has been shown to be dictated by gravity, peristaltic gastrointestinal movement, and the mechanics of the negative pressure generated by movement of the diaphragm.…”
Section: Introductionmentioning
confidence: 99%